Pathological examination and bacterial re-isolation by culture and PCR of experimental Ornithobacterium rhinotracheale infection in broiler chickens - Kilic, A.; Timurkaan, N.; Ertas, H. B.; Yilmaz, F. (Ecole Nationale Veterinaire Toulouse, 2009)
The objective of the present study was to investigate the pathogenicity of the Ornithobacterium rhinotracheale (ORT) B3263/91 (serotype A) strain inoculated alone (4.8x10(8) CFU) to 14 day old broiler chickens (n=30) by the aerosol route whereas 30 not treated birds served as negative controls. After inoculation, birds were clinically examined and weighted and histological, microbiological (culture) and molecular (PCR) analyses were performed on different parts of the respiratory tree (sinuses, larynx, trachea, lungs and air sacs) and on visceral organs collected from 10 birds of each group on the weeks 1, 2 and 3 following experimental ORT inoculation. The clinical signs (rules, gasping and mucus discharge) peaked between the 5(th) and the 9(th) days in 10% of treated birds. Focal epithelial hyperplasia associated with necrosis and inflammatory lesions (oedema, blood vessel congestion and moderate inflammatory infiltration) of the lamina propria of the upper parts of the respiratory tract and of air sacs, as well as around bronchioles and in BALT in some lung areas were observed within the first 3 weeks, lungs being more belatedly affected than upper parts. In parallel, ORT was successfully re-isolated by culture and PCR from trachea and lungs. These results show that this ORT strain acts as a primary infectious agent of the respiratory tract even if the induced lesions were transient and mainly located in air sacs and suggest the involvement of other viral and bacterial infections for disease amplification.
Keywords: Ornithobacterium rhinotracheale; broiler chickens; culture; PCR; histopathological findings